Political economy of the energy sector in Cameroon - Lenjo, Daren Semo Joko Che (My University, 2021)
ContentsACKNOWLEDGMENTiABSTRACTiiFiguresivTablesvAbbreviationsviCHAPTER 11INTRODUCTION1CHAPTER 24ENERGY AND POLITICAL ECONOMY THEORIES42.1 Mercantilism42.1.1 The History of Mercantilism52.1.2 Criticisms of Mercantilism72.1.3 Mercantilism and the Energy Sector82.2 Marxism92.2.1 Marxism, Anthropology, and Feminism102.2.2 Criticisms of Marxism132.2.3 Marxism and the Energy Sector142.3 Economic Liberalism152.3.1 Free Market and Free Trade162.3.3 Economic Liberalism and the Energy Sector172.4 Summary of Chapter19CHAPTER 321THE GLOBAL ENERGY SECTOR213.1 Development of the Global Energy Sector213.2 Sub-sectors of Energy233.3 Economic Implications of the Global Energy Sector343.3.1 Capital and Investment343.3.2 Labour and Employment353.3.3 Energy Prices373.4 World Total Energy Supply383.5 Future Trends in The Global Energy Sector403.6 Summary42CHAPTER 444CAMEROON’S ECONOMY AND THE ENERGY SECTOR444.1 Cameroon’s Economy444.1.1 Gross Domestic Product444.1.2 Unemployment Rate454.1.3 The Consumer Price Index (CPI)464.1.4 Foreign Trade464.1.5 Foreign Direct Investment524.1.6 Price of Crude Oil534.2 The Energy Sector534.2.1 Fossil Fuels544.2.2 Oil544.2.3 Natural Gas564.2.4 Coal574.2.5 Biomass584.2.6 Hydropower584.2.7 Others604.3 Summary61CHAPTER 563POLITICAL ECONOMY OF THE ENERGY SECTOR IN CAMEROON635.1 The Political Context of Cameroon635.2 The Importance of Cameroon’s Energy Sector in the World and Africa645.2.1 Energy Supply645.2.2 Energy Consumption735.2.3. A Comparison of Energy Sector: World, Africa and Cameroon845.3 Energy Policies in Cameroon885.4 Privatization and Liberalization of the Energy Sector in Cameroon905.5 Critics of the Energy Sector in Cameroon925.6 Summary95CONCLUSION97REFERENCES100ABSTRACTThe aim of this thesis is to evaluate the energy sector in terms of political economy. The energy sector is a sector which should be examined both economically and politically. The research was broadly qualitative and mildly quantitative, information was mostly gotten from journals, articles, books and other publications. In the quantitative aspect, a comparison between world, Africa and Cameroon energy supply and consumption was made, this was done to indicate the importance of Cameroon’s energy sector to Africa then to the world. The results show that the government’s interaction with its energy sector is being poorly affected by corruption, insufficient FDI and limited privatization of the energy sectors. Therefore, in conclusion in order to achieve and effective and efficient energy sector, the economic liberalisation of the sector is needed, this leads to free participation, open competition, better international relations, and more foreign investment which will positively affect economic growth in the country.

ABSTRACTThe aim of this thesis is to evaluate the energy sector in terms of political economy. The energy sector is a sector which should be examined both economically and politically. The research was broadly qualitative and mildly quantitative, information was mostly gotten from journals, articles, books and other publications. In the quantitative aspect, a comparison between world, Africa and Cameroon energy supply and consumption was made, this was done to indicate the importance of Cameroon’s energy sector to Africa then to the world. The results show that the government’s interaction with its energy sector is being poorly affected by corruption, insufficient FDI and limited privatization of the energy sectors. Therefore, in conclusion in order to achieve and effective and efficient energy sector, the economic liberalisation of the sector is needed, this leads to free participation, open competition, better international relations, and more foreign investment which will positively affect economic growth in the country.
Keywords: Finance; Maliye; Political EconomyEnergy SectorPrivatization Political EconomyEnergy SectorPrivatization